Konsep Pendidikan Multikultural Berbasis Islam Dan Peranannya Terhadap Persatuan Indonesia - Wahyu Adinda Nur Ashifa; Abidah Nabilah; Ananda Fauziah; Raysita Syahnas Sharon; Muhamad Basyrul Muvid (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
Multiculturalism can be understood as an acknowledgment of the diversity of a pluralistic, heterogeneous and plural society. If expanded, it can also be interpreted as a diversity of cultures, traditions, lifestyles, religions, and other forms of difference. For the Indonesian people who are indeed blessed with God Almighty, this plurality and plurality should be a source of pride and great strength for the Indonesian nation. Multiculturalism is not only recognized but also accepted for differences, ethnicity, religion, race, between groups and ethnicities. The Indonesian people who live in it must be able to live side by side with each other, so that the desired harmonization of the Indonesian people can be realized properly. difference with Pancasila (nothing else). As a unifying ideology of the nation, Pancasila is a solution to conflicts between nationalist and religious groups, Pancasila has been able to show its function as a unifier of the plural, heterogeneous, and multicultural Indonesian nation.